Leaf Extract of Markhamia platycalyx: Polyphenolic Profile, Acute Toxicity, Anti-inflammatory, Hepatoprotective and in vitro Antioxidant Activities - El Dib, R. A.; Gaara, A. H.; El-Shenawy, S. M.; Micky, J. A. A.; Mohammed, A. A.; Marzouk, M. S. (Drug Research, 2014)
10 polyphenols were identified from 80% aqueous methanol extract (AME) of Markhamia platycalyx [(Baker) Sprague] leaf. Their structures were characterized as protocatechuic acid (1), E-caffeic acid (2), E-methyl caffeate (3), isoverbascoside (4), verbascoside (5), jacraninoside-I (6), cosmosiin (7), cinaroside (8), luteolin (9) and apigenin (10) based on chemical and extensive spectral studies (UV, ESI-MS, 1H, 13C and 1D/2D NMR). Biological evaluation indicated that AME is non-toxic to the experimental animals. It exhibited a significant inhibition of oedema after 1, 2, 3 and 4 h for all examined doses (250, 500 and 1 000 mg/kg). In comparison with silymarin, the AME demonstrated a significant hepatoprotective effect in the form of high reduction in elevated ALT and AST serum levels in regard to paracetamol treated group. As well as, it revealed a marked significant scavenging activity by 62.9, 82.5, 88.3, 83.7 and 83.7%, for the concentrations 20, 40, 60, 80 and 100 mg/ml of the extract, respectively, relative to L-ascorbic acid (86.8%), which was used as a reference antioxidant drug.
Keywords: Bignoniaceae; Markhamia platycalyx leaf; acute toxicity; hepatoprotection; anti-inflamatory; in vitro antioxidant